Dynamic mechanical response and weldability of high strength 7A62 aluminum alloy. (March 2020) - Zhou, G X; Lang, Y J; Du, X Zh; Mao, H; Li, J B; Wang, Sh; Qiao, L; Cai, H
Abstract: The 7A62 as one kind of Al-Zn-Mg alloys is the highest strength weldable aluminum alloy currently. Plates and forgings of 7A62 alloy have been widely used in the defense system and main bearing parts of special vehicles. The microstructure, dynamic mechanical response and weldability of 7A62 aluminum alloy were investigated by OM, TEM, SHTB, DSC, microhardness and other tests. The morphology and mechanical test results showed that the 7A62 aluminum alloy strengthened by trans-scale precipitates had high strength, high hardness and good plastic toughness. The mechanical responses of the 7A62 aluminum alloy were found to be strain-rate sensitive and the dynamic response behavior was significantly higher than that of the 7A52 aluminum alloy through the SHTB test. In addition, for the as-welded 7A62 the tensile strength reached a scope of 260 MPa-305 MPa, which is considerably higher than the tensile properties reported when using ER5356. Because the weld of 7A62 alloy was free of macroscopic imperfections. The grains were highly equiaxed and homogeneous throughout the melting zone, showing smooth grain boundaries. Compared with 7A52, the lower melting point, low thermal enthalpy and low specific heat capacity of 7A62 alloy are more conducive to weld performed.